2022
DOI: 10.1017/s174413312200024x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of public long-term care insurance on the medical service use by older people in South Korea

Abstract: Public long-term care insurance (LTCI), which provides home and institutional care benefits, was introduced in July 2008 in South Korea. This study aims to evaluate the effects of the introduction of LTCI on older people's medical service use, including outpatient visits, inpatient services and longer stays (181 days or longer) in hospitals by implementing a quasi-experiment design with a generalised difference-in-difference method. The results showed that the introduction of LTCI did not change the use of out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Similar to previous studies [28,29], the results of this study also suggest that LTCI effectively reduces hospitalization health service utilization among middle-aged and elderly adults. Unlike the study by Chao Ma et al, this study found that the effect of LTCI on outpatient health service utilization was not significant, possibly because of the difference in the chosen study sites.…”
Section: Effect Of Ltci On Health Service Utilization Of Middle-aged ...supporting
confidence: 90%
“…Similar to previous studies [28,29], the results of this study also suggest that LTCI effectively reduces hospitalization health service utilization among middle-aged and elderly adults. Unlike the study by Chao Ma et al, this study found that the effect of LTCI on outpatient health service utilization was not significant, possibly because of the difference in the chosen study sites.…”
Section: Effect Of Ltci On Health Service Utilization Of Middle-aged ...supporting
confidence: 90%